Apple polyphenol extract alleviates lipid accumulation in free‐fatty‐acid‐exposed HepG2 cells via activating autophagy mediated by SIRT1/AMPK signaling. (9th October 2020) - Li, Deming; Cui, Yuan; Wang, Xinjing; Liu, Fang; Li, Xinli
Abstract : Defective degradation of intracellular lipids induced by autophagy is causally linked to the development of non‐alcoholic fatty liver disease (NAFLD). Natural agents that can restore autophagy could therefore have the potentials for clinical applications for this public health issue. Herein, we investigated the effects of apple polyphenol extract (APE) on fatty acid‐induced lipids depositions in HepG2 cells. APE treatment alleviated palmitic acid and oleic acid‐induced intracellular lipid accumulation, concomitant with the increased autophagy, restored lysosomal acidification, inhibited lipid synthesis and slight promotion of fatty acid oxidation. Mechanistically, APE up‐regulated the expression of SIRT1, activated LKB1/AMPK pathway and inhibited mTOR signaling. Over‐expressed or knock‐down SIRT1 positively regulated AMPK and ATG7 expressions. SIRT1 and ATG7 knock‐down impaired APE induction of improved lipid accumulation, increased intracellular TG content. Thus, APE induction of autophagy to ameliorate fatty acid‐induced lipid deposition is SIRT1 dependent, APE conserved preventive potentials for clinical hepatosteatosis.